miR-205 in situ expression and localization in head and neck tumors - a tissue array study - Cheah, Yoke Kqueen; Ab Mutalib, Nurul Syakima; Lee, Learn Han (Asian Pacific Organization for Cancer Prevention, 2015)
Background: microRNAs are small non-coding RNA that control gene expression by mRNA degradation or translational inhibition. These molecules are known to play essential roles in many biological and physiological processes. miR-205 may be differentially expressed in head and neck cancers; however, there are conflicting data and localization of expression has yet to be determined. Materials and Methods: miR-205 expression was investigated in 48 cases of inflammatory, benign and malignant tumor tissue array of the neck, oronasopharynx,larynx and salivary glands by Locked Nucleic Acid in situ hybridization (LNA-ISH) technology. Results: miR-205 expression was significantly differentially expressed across all of the inflammatory, benign and malignant tumor tissues of the neck. A significant increase in miR-205 staining intensity (p<0.05) was observed from inflammation to benign and malignant tumors in head and neck tissue array, suggesting that miR-205 could be a biomarker to differentiate between cancer and non-cancer tissues. Conclusions: LNA-ISH revealed that miR-205 exhibited significant differential cytoplasmic and nuclear staining among inflammation, benign and malignant tumors of head and neck. miR-205 was not only exclusively expressed in squamous epithelial malignancy. This study offers information and a basis for a comprehensive study of the role of miR-205 that may be useful as a biomarker and/or therapeutic target in head and neck tumors.